2017
DOI: 10.3813/aaa.919094
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of Acoustic Environment Simulator to Determine the Relationship between Sound Objects and Soundscape

Abstract: SummaryAn acoustic environment simulator is a system that facilitates acoustic environment composition by controlling the parameters of sound objects (both background and sound events), allowing the user to compose and compare soundscapes against their expectations. By using the acoustic environment simulator, data regarding parameters of sound objects, such as their sound level and selection, can be obtained. Furthermore, these data can be used to understand the relationship between the sound objects and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…They also found distinguishable or indistinguishable, background or foreground, and intrusive or smooth are three important dimensions in terms of sound sources [40]. Sudarsono et al [17] revealed that three reliable soundscape dimensions are relaxation, dynamics and communication, which are consistent with the previous study conducted by Kang and Zhang [37]. Meng et al also found that acoustic comfort correlated with subjective loudness [18].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…They also found distinguishable or indistinguishable, background or foreground, and intrusive or smooth are three important dimensions in terms of sound sources [40]. Sudarsono et al [17] revealed that three reliable soundscape dimensions are relaxation, dynamics and communication, which are consistent with the previous study conducted by Kang and Zhang [37]. Meng et al also found that acoustic comfort correlated with subjective loudness [18].…”
Section: Introductionsupporting
confidence: 74%
“…Soundscapes, defined by ISO, are acoustic environment as perceived or experienced and/or understood by a person or people, in context [14]. In soundscape studies, different facets have been investigated, termed as soundscape dimensions, characteristics, factors, attributes etc., representing the general perception tendencies of soundscape, specific perception of soundscape, and objective measurement of soundscape [15,16,17,18], although those terms are often used in a mixed way.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the fact that people prefer landscapes with bird sounds to those with traffic sounds. The principal component analysis (PCA), a statistical method was proposed to explore communalities in collected soundscape semantical data, and Kaiser-Meyer-Olkin (KMO) was applied within PCA to verify the adequacy of the data and the factor loadings [18][19][20]22]. The PCA with varimax rotation was thus chosen to extract the orthogonal factors (Table 3).…”
Section: Soundscape In Multidimensional Scales In Vr Simulationsmentioning
confidence: 99%
“…The reproduction by using a headphone has also been implemented but there is limited information about the validity of the system. The sonic environment simulation using a multi-speaker system also has been validated using semantic differential analysis [34].…”
Section: Figurementioning
confidence: 99%
“…Sudarsono et al [34] further developed the simulator, enabling the composition of a sonic environment using only the sound sources. This simulator can also simulate the movement of moving sound sources and the position of the sound sources.…”
Section: Figure 5 Sonic Reproduction System Using Speakersmentioning
confidence: 99%